(untitled) (Revista Brasileira Multidisciplinar, 2026)
In recent years, Hermetia illucens has attracted increasing interest as an organic waste converter. The larvae of this species feed voraciously on various types of organic waste, including food waste, agro-industrial by-products, and agricultural waste, in a shorter period than conventional composting. Bioconversion using H. illucens larvae (BSFL) is an attractive option, considering it represents a potentially valuable solution to two problems: organic waste management and the growing global demand for food. The use of BSFL in animal feed has gained increasing prominence in recent decades due to its nutritional benefits, sustainability, and effectiveness in animal feed production. These larvae have shown themselves to be a promising alternative to diversify animal protein sources, reduce dependence on scarce resources such as soybeans and fish, and mitigate environmental impacts associated with conventional feed production. In this introduction, we will explore the main aspects of the use of BSFL in animal feed, including its nutritional characteristics, as well as the challenges and prospects of this innovative approach to feeding farmed animals.